The universe in your hand : a journey through space, time, and beyond - Galfard, Christophe (Flatiron Books, 2016)
"Christophe Galfard's mission in life is to spread modern scientific ideas to the general public in entertaining ways. Using his considerable skills as a brilliant theoretical physicist and successful young adult author, The Universe in Your Hand employs the immediacy of simple, direct language to show us, not explain to us, the theories that underpin everything we know about our universe. To understand what happens to a dying star, we are asked to picture ourselves floating in space in front of it. To get acquainted with the quantum world, we are shrunk to the size of an atom and then taken on a journey. Employing everyday similes and metaphors, addressing the reader directly, and writing stories rather than equations renders these astoundingly complex ideas in an immediate and visceral way." --